2021
DOI: 10.1186/s12931-021-01801-0
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of type I and III collagen predicts progression of idiopathic pulmonary fibrosis

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is characterized by the accumulation of fibrillar collagens in the alveolar space resulting in reduced pulmonary function and a high mortality rate. Biomarkers measuring the turnover of type I and III collagen could provide valuable information for prognosis and treatment decisions in IPF. Methods Serological biomarkers reflecting the formation of type III collagen (PRO-C3) and degradation of type I (C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
(39 reference statements)
2
19
0
1
Order By: Relevance
“…In view of the important contribution of collagen to the mechanical stiffness of pulmonary fibrosis, collagen turnover has naturally become an important means for monitoring disease progression and predicting patient prognosis. Increased concentrations of the collagen degradation markers type 1/3/6 collagen, and C-reactive protein are associated with an increased risk of overall mortality, and elevated levels of the collagen synthesis markers Pro-C3 and Pro-C6 are associated with IPF progression ( Organ et al, 2019 ; Jessen et al, 2021 ).…”
Section: Important Cells and Extracellular Matrix Involved In The Pat...mentioning
confidence: 99%
“…In view of the important contribution of collagen to the mechanical stiffness of pulmonary fibrosis, collagen turnover has naturally become an important means for monitoring disease progression and predicting patient prognosis. Increased concentrations of the collagen degradation markers type 1/3/6 collagen, and C-reactive protein are associated with an increased risk of overall mortality, and elevated levels of the collagen synthesis markers Pro-C3 and Pro-C6 are associated with IPF progression ( Organ et al, 2019 ; Jessen et al, 2021 ).…”
Section: Important Cells and Extracellular Matrix Involved In The Pat...mentioning
confidence: 99%
“…Measures of the serum levels of matrix metalloproteases that break down collagens type I and III using enzyme‐linked immunosorbent assays may lead to a clinically relevant IPF biomarker. 153 As we try new IPF treatment approaches, the importance of accurate, reliable, reasonably priced assays to monitor the efficacy for clinical trial and real‐world application will be increasingly important.…”
Section: Biomarkers and Assessing Treatment Responsementioning
confidence: 99%
“…PROFILE was one such study, which identified SP-D and CA125 as biomarkers that predict disease progression and death in IPF [ 13 ]. Likewise, results from the ongoing Pulmonary Fibrosis Biomarker cohort showed that longitudinal levels of type I and III collagen turnover were associated with progressive disease [ 55 ].…”
Section: Challenges Of and Approaches To Realising The Full Potential...mentioning
confidence: 99%